“Just go back to your place!” Women and the Politics of Contested Public Spaces - Roncalli, Elvira (HannahArendt.net, 2024)
Women have been part of political movements and uprisings throughout the modern age. Why is it that the overall perception is otherwise, namely that the political and public sphere are inimical, if not hostile to women and that “women’s place” is considered to be elsewhere, above all away from the light of the public? In my essay I examine the notion of “public space/spaces” understood in the Arendtian sense of a space that is created when people, in their plurality, come together as exemplify by women’s action within the Italian Resistenza. That women’s presence in public spaces appears still contentious is indicative of a notion of the political that precludes and excludes women as speakers and as agents, the legacy of a past that has forced women to the private sphere calling it “their place.” It is therefore crucial to revisit the relationship between“public” and “private” so that the complex play of visibility-invisibility, of political affirmation and political exclusion come fully to the fore, and the public space reveals itself as the site for reinforcing existing relations but also the site for their subversion.